2004
DOI: 10.1103/physrevlett.92.134301
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Stick-Slip to Continuous Sliding in Atomic Friction: Entering a New Regime of Ultralow Friction

Abstract: A transition from stick-slip to continuous sliding is observed for atomically modulated friction by means of a friction force microscope. When the stick-slip instabilities cease to exist, a new regime of ultralow friction is encountered. The transition is described in the framework of the Tomlinson model using a parameter eta which relates the strength of the lateral atomic surface potential and the stiffness of the contact under study. Experimentally, this parameter can be tuned by varying the normal load on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
485
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 536 publications
(536 citation statements)
references
References 12 publications
39
485
2
3
Order By: Relevance
“…In theory, this amplitude can be changed by varying the normal load 10,16 although it is worth noting that a change in the normal load is probably changing other parameters of the system in a nontrivial way. The effect of this disorder is a small change in the potential shape ͑see Fig.…”
Section: Dmentioning
confidence: 99%
“…In theory, this amplitude can be changed by varying the normal load 10,16 although it is worth noting that a change in the normal load is probably changing other parameters of the system in a nontrivial way. The effect of this disorder is a small change in the potential shape ͑see Fig.…”
Section: Dmentioning
confidence: 99%
“…Whereas rate and state models have been used to describe the freeze-melting transition cycles in the case of lubricated systems studied with the surface force apparatus (SFA). 29 The Prandtl-Tomlinson model is frequently used to describe stick-slip motion 30,31 which is particularly relevant to AFM measurements. In this simple model, the AFM tip,…”
mentioning
confidence: 99%
“…32,33 It is also able to describe many useful properties of dry friction, for instance the in uence of system parameters such as sti ness as well as the potential amplitude and periodicity on the transition between stick-slip and continuous friction regimes. 31 The use of an interaction potential, however, implies that important information regarding both the properties of the tip (e.g. material properties, radius of curvature) and the contact surfaces ( e.g.…”
mentioning
confidence: 99%
“…We would like to point out that researchers working on different size scales observed a decrease of the COF of graphite as a consequence of dynamic instabilities [15,28,29]. This is probably because they observed the same phenomena that was already studied by Oden and coworkers [30,31], who found that the well-known reduction in the COF with an increase in sliding speed is a consequence of the dynamic instability of stick-slip phenomena on the atomic scale.…”
Section: Introductionmentioning
confidence: 68%
“…By measuring the atomic-scale friction as a function of the rotation angle of a graphite mono-crystal they found a region of COF decrease of more than one order of magnitude. Further experimental work on the topic of superlubricity [29] revealed that the reason for the ultra-low friction could be the transition from stick-slip phenomena (with the periodicity of the graphite hexagonal crystal lattice) to continuous sliding.…”
Section: Introductionmentioning
confidence: 99%